Hydrodeoxygenation of lignin related phenolic monomers in polar organic electrolyte via electrocatalysis in a stirred slurry catalytic reactor - Wijaya, Yanuar Philip; Smith, Kevin J.; Kim, Chang Soo; Gyenge, Elod L. (Royal Society of Chemistry, 2022)
Electrocatalytic hydrodeoxygenation of lignin model compounds (cerulignol, creosol, guaiacol, phenol and their mixture) has been performed under mild conditions (1 atm, 25-60 degrees C) using a stirred slurry cathode catalytic reactor and a three-component electrolyte system: methanesulfonic acid - isopropanol - inorganic salt (KCl or NaCl). Fully saturated and deoxygenated products, such as propylcyclohexane, were obtained with high selectivity (up to 40%) and conversion (up to 90%) after 4 h of reaction time. A dual catalytic function for hydrogenation and dehydration is provided by the dispersed metal catalyst (Pt/C) and acidic protons from the electrolyte, respectively. The addition of isopropanol to the electrolyte is crucial for substrate solubilization and favoring the complete hydrodeoxygenation reaction pathways. Furthermore, the presence of salt (e.g., KCl or NaCl) in the electrolyte improved the conversion, faradaic efficiency, and carbon balance, due possibly to stabilization of protonated reactive intermediates. This study demonstrates that production of complete hydrodeoxygenation species (i.e., cyclic hydrocarbons) from diverse lignin related phenolics can be achieved via electrocatalysis at significantly lower temperatures and pressures than those in traditional thermal catalysis, in the absence of external hydrogen gas and without catalyst coking. Therefore, electrocatalysis provides new opportunities for chemical and fuel production using biomass-derived renewable feedstock.